Identification of the risk of anterior cruciate ligament injury by muscle strength balance assessment - Yuliana, Ela; Diyananda, Dzulfiqar; ., Yuliasih (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
This study aims to identify the risk of anterior cruciate ligament (ACL) injury in petanque athletes at Jakarta State University (UNJ). This research is a quantitative descriptive study using a cross-sectional survey design. There were 18 research subjects consisting of 10 male athletes and 8 female athletes. Characteristics of research subjects such as body weight and Body Mass Index (BMI) were measured using the Xiaomi MI scale. Assessment of hamstring and quadriceps muscle strength is assessed using an electromyography (EMG) tool when performing manual muscle testing (MMT). The research results showed that the research subjects had a normal BMI category, namely 22.31 for men and 22.09 for women. Statistically, there were no significant differences in hamstring and quadriceps muscle strength in the right (p=0.448) and left (p=0.376) legs for male subjects. Meanwhile, for female subjects, there was also no significant difference found between hamstring and quadriceps muscle strength on the right (p=0.429) and left (p=0.232) legs. Thus, it can be concluded that UNJ petanque athletes have a low risk of ACL injury, because they have hamstring and quadriceps muscle strength that is not significantly different (balanced), and is supported by a normal BMI category. Further studies need to be carried out by combining and considering other variables in identifying the risk of ACL injury.Key word:  anterior cruciate ligament injury, electromyography, muscle strength balance